Spatial distribution and aggregation of human-environment coordination and optimal paths in the Yellow River Delta, China. (October 2022) - Zhu, Wenjun; Muhammad, Ali; Han, Mei; Li, Yunlong; Kong, Xianglun; Kong, Fanbiao
Highlights: A quantitative study of human-environment coordination on spatiotemporal change. Spatial aggregation technology adoption for evaluating human-environment coordination. Coordination of human-environment in the Yellow River Delta is lost on the coast. Human-environment coordination had strong spatial aggregation in the coastal areas of YRD. Abstract: Human-environment relationship, as the interaction between human society and natural environment, is the inevitable way for sustainable development. The coordinated relationship between human and environment determines the quality of regional economic development and ecological environment. To coordinate human-environment relationship for natural resources can support human society development, we investigated the dynamic evolutionary characteristics of the human-environment coordination of the Yellow River Delta over the past 30 years using the coupled coordination model, artificial classification and spatial autocorrelation analysis. From the analytical results, the findings are as follows: (1) Human activity intensity in the Yellow River Delta increased to 35.24 % from 1990 to 2018, which spatial distribution pattern showed low in the coastal and high inland. Ecological carrying capacity was decreased by 1.61 × 10 4 hm 2 . The spatial distribution pattern showed the same characteristics as human activity intensity. (2) The area of human-environment coordination showed increasing trend from 1990 to 2018. Among them, "Severe Uncoordinated" and "High-quality Corrdianted" area changed the most obviously, the area of this two coordinated levels were increased by 731.15 km 2 and 674.33 km 2 respectively. "Good Coordinated" area dramatically decreased 1 479.61 km 2, "Relatively Uncoordinated" and "Low Coordianted" were stable in the study area; (3) The coordination of human-environment indicates clear spatial agglomeration characteristics that, high aggregation in the coastal but low inland. Moreover, the research provides references for coordinating human-environment relationship.